Li-Fraumeni Syndrome: Elucidation of the Mechanisms of Cancer Initiation that Began at Hiroshima - MALKIN, David; TSUCHIDA, Rika (The Japanese Journal of Pediatric Hematology, 2005)
Although most pediatric oncologists are aware that Li-Fraumeni syndrome (LFS) is characterized by germline p53 mutations, few appreciate that the discovery of this syndrome in 1969 ultimately finds its origins in the detailed epidemiological investigations of cancer in the victims of the atomic bomb at Hiroshima. Both Dr. Robert W. Miller, a pediatrician who became Director of the U.S. National Cancer Institute, and many Japanese pediatricians and paramedical staff from the Atomic Bomb Casualty Commission (ABCC) Pediatrics Study expended enormous efforts to clarify this relationship. The importance of the study of cancer clusters to better understand cancer etiology is derived from their work. We now understand LFS to be a rare autosomal dominantly inherited familial cancer predisposition syndrome characterized by malignancies of both epithelial and mesenchymal origin including soft tissue sarcomas, breast cancer, osteosarcoma, leukemia, brain tumors and adrenocortical carcinoma. In 1990, constitutional mutations of the p53 tumor suppressor gene were shown to be responsible for LFS, a discovery that defined cancer as a genetic disease. Since then, LFS has been the subject of intense clinical and fundamental biological investigation. Recent studies suggest that the types of tumors that develop may in part be determined by the specific p53 mutation, and that murine models of p53 dysfunction accurately reflect the LFS phenotype, providing in vivo models with which to study p53-mediated mechanisms of carcinogenesis. Whereas approximately 70% of LFS is associated with p53 mutations, the cause of the remaining 30% are generally unknown. This unpredictability of genetic penetrance raises numerous ethical issues related to genetic testing and clinical surveillance. This year, 2005, is the 60th anniversary of the bombing of Hiroshima, an appropriate time to review what is known about LFS, the paradigm cancer predisposition syndrome.